2014
DOI: 10.1111/1469-0691.12591
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B immunity in teenagers vaccinated as infants: an Italian 17-year follow-up study

Abstract: We assessed the persistence of hepatitis B surface antigen antibody (anti-HBs) and immune memory in a cohort of 571 teenagers vaccinated against hepatitis B as infants, 17 years earlier. Vaccinees were followed-up in 2003 and in 2010 (i.e. 10 years and 17 years after primary vaccination, respectively). When tested in 2003, 199 vaccinees (group A) had anti-HBs <10 mIU/mL and were boosted, 372 (group B) were not boosted because they had anti-HBs ≥10 mIU/mL (n = 344) or refused booster (n = 28) despite anti-HBs <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…Previous studies have shown that the protection given by the HBV vaccine lasts at least 15-20 years [28,29]. Our findings showed anti-HBs titers declined with time, but when adjusted for age, this decline was not significant.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies have shown that the protection given by the HBV vaccine lasts at least 15-20 years [28,29]. Our findings showed anti-HBs titers declined with time, but when adjusted for age, this decline was not significant.…”
Section: Discussioncontrasting
confidence: 74%
“…Thus, despite the loss of antibody many vaccinated individuals maintain active immune memory and show a strong anamnestic response following a booster dose of vaccine (the so-called boostability) given up to 20-25 y. [8][9][10][11][12] However other studies, mainly conducted in Asiatic countries, indicate that immune memory starts to wane during the second decade after vaccination still arising the question whether there is a need of a booster dose to maintain long-term immunity. 13,14 The aim of this study was to assess the duration of anti-HBs antibody and immune memory in a cohort of teenagers vaccinated as infants and in a cohort of young adults vaccinated as adolescents, 18-19 y earlier.…”
Section: Introductionmentioning
confidence: 99%
“…A typical anamnestic response is characterised by a rapid 10-100-fold increase in specific antibodies, which starts 5-8 days after the re-exposure to the antigen and peaks after about 14 days [2][3][4]. HBsAg-specific memory has been shown to persist for at least 15-17 years after immunisation [5][6][7]. Long-term follow-up studies have shown that clinical HBV-disease or HBsAg-carrier status rarely occur among successfully vaccinated individuals, even in the case of anti-HBs titres <10 IU/l [8].…”
Section: Introductionmentioning
confidence: 99%